Upaya Meningkatkan Kebugaran Jasmani Melalui Pendekatan Permainan Tradisional Kelas X-3 SMA Negeri 1 Gedangan Sidoarjo - Mohammad Roisul Umam; Sasminta Christina Yuli Hartati; Supriyanto Supriyanto (Journal of Creative Student Research, 2024)
This study examines the low interest of class X-3 students at SMAN 1 Sidoarjo in physical fitness activities. The aim is to evaluate the effectiveness of traditional game-based learning methods in improving students' physical fitness. The research uses an action approach with stages of planning, implementation, observation, and reflection. The sample consists of 36 students from class X-3 SMAN 1 Sidoarjo who were observed during the pre-cycle, cycle 1, and cycle 2. Data was collected through observation, interviews, and documentation, then analyzed qualitatively and quantitatively using percentages. Research findings indicate an improvement in student learning outcomes after the implementation of traditional game-based learning methods in cycles I and II. This suggests that the approach is effective in increasing the level of physical fitness and student participation in physical education activities.